DETERMINANTS OF EMPLOYEE JOB SATISFACTION: EVIDENCE FROM THE UNIVERSITY OF KARACHI, PAKISTAN - Sabbor Hussain; John Francis Diaz (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2020)
The study identified factors affecting employee job satisfaction in the University of Karachi. The research collected data using survey questionnaire consisting of twenty-nine questions. The study found that a generous rewards and compensation packages lead to job satisfaction and are affected by promotion and job security. Good working relationship with co-workers also contributes to employee job satisfaction. Also, it is found that good working environment also contributes to employee motivation, and is influenced by better facilities, and training and development. Finally, good supervision provides motivation that enhances the quality of output and employee performance. The findings are important, because it is well-established in the literature that job satisfaction and employee motivation play a major role in increasing productivity of employees and profitability of the organization.